Microsurgical reconstruction for post-traumatic defects of lower leg in the elderly: A comparative study - Xiong, Lingyun; Gazyakan, Emre; Wähmann, Matthias; Bigdeli, Amir; Kremer, Thomas; Harhaus-Wähner, Leila; Sun, Jiaming; Kneser, Ulrich; Hirche, Christoph (Injury, 2016)
ABSTRACTS - Background - Lower leg microsurgical reconstruction in the elderly is challenging, especially for post − traumatic defects. The present study aimed to evaluate the risk factors, management and outcome of free tissue transfer in patients older than 65 years of post-traumatic defects. - Methods - Retrospective chart review was performed for all patients older than 18 years undergoing free tissue transfer for post-traumatic lower leg reconstruction from April 2000 to November 2014. A comparative study was designed to identify risk factors and outcome. - Results - In total, 197 patients (ages 18-64) and 44 patients (ages ≥65, average 71.7±6.3) were included and allocated into cohort 1 and 2, respectively. Cohort 2 had a higher rate of diabetes mellitus and/or peripheral artery disease (46.6%, P<0.01). There was no significant difference in major flap complications, donor site complications and amputation rates (P>0.05). A higher rate of intensive care unit (ICU) admission was observed in cohort 2 (37.8%, P<0.01). Comparable limb salvage rates were recorded (97.1% and 95.6%, P=0.59) with an average follow-up of 25.9±30.1months in cohort 1 and 23.7±16.6months in cohort 2. - Conclusion - Post-traumatic microsurgical free tissue transfer to the lower leg can be performed safely in patients older than 65 years with high success rate and manageable complications.
Gesehen am 28.09.2021